2014
DOI: 10.4304/jmm.9.8.1040-1047
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Study on Ventilation & Cooling for Main Transformer Room of an Indoor Substation

Abstract: Based on natural ventilation design scheme for main transformer room of an indoor substation, different air distribution schemes were obtained by changing height and size of air inlets and outlets. Three-dimensional simulation of air distribution was conducted for the transformer room by using Computational Fluid Dynamics (CFD) method. Ventilation & cooling effect of different indoor ventilation schemes were simulated with software FLUENT. By analyzing velocity fields and temperature fields, influences of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In certain cases, the solution involves the construction of underground substations to increase the offer of power, which, despite being the most feasible type in specific situations, still present several drawbacks, such as limited room for the dissipation of the heat generated by the transformer [3]- [5].…”
Section: Introductionmentioning
confidence: 99%
“…In certain cases, the solution involves the construction of underground substations to increase the offer of power, which, despite being the most feasible type in specific situations, still present several drawbacks, such as limited room for the dissipation of the heat generated by the transformer [3]- [5].…”
Section: Introductionmentioning
confidence: 99%
“…In the open literature, limited number of work were found on the study of optimum ventilation of transformer building. A few works were found on the investigation of the efficiency of indoor substation by simulation [1][2]. It was concluded that height elevation between air outlet and inlet will improve the indoor temperature and velocity fields [2].…”
Section: Introductionmentioning
confidence: 99%
“…A few works were found on the investigation of the efficiency of indoor substation by simulation [1][2]. It was concluded that height elevation between air outlet and inlet will improve the indoor temperature and velocity fields [2]. For a typical transformer heat map, the hottest spot was usually located at the top surface, followed by the sides of transformer [3].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported in [6] how finite element approach is applied on oil filled disc type windings for the purpose of locating hot spot. Cases regarding optimal design of indoor substation and ventilation are treated in [7,8,9,10,11]. There is even an example where FEM CFD tools were used to gain further insight in conjugate heat transfer for oil inside and air outside the radiators for both ONAN and ONAF transformers [12,13].…”
Section: Introductionmentioning
confidence: 99%